Total Ionization Cross Sections of $NO_2$, $CO$ and $CS$ Molecules Due to Electron Impact (Journal of Atomic and Molecular Sciences, 2013)
The total cross sections for $NO_2$, $CO$ and $CS$ have been calculated by Binary-Encounter-Bethe [BEB] method of Khare from threshold energy to 10 MeV due to electron impact. This model has been developed by combining the useful features of Plane Wave Born Approximation (PWBA) and BEB model of Kim. It is shown that Bethe and Mott cross section terms differ from those of the Kim [BEB] method but their sums are very close to other. Results are presented with the help of graphs. Adequate comparisons of collisional parameter have been made with other available experimental values. The calculated cross-sections are compared extensively with a number of all possible experimental data and theoretical results.